Physicochemical characterization of new hybrids and inbred lines of papaya - Reis, Ronielli Cardoso; Viana, Eliseth de Souza; Jesus, Jaciene Lopes de; Dantas, Jorge Luiz Loyola; Lucena, Rangel Sales (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate papaya genotypes as to their physical and physicochemical characteristics, in order to identify the most promising ones as new commercial cultivars. Analyses of length, diameter, internal cavity diameter, mass, pulp thickness, firmness of fruit with peel, pulp firmness, pulp color, titratable acidity, soluble solids, pH, total carotenoids, and vitamin C were performed in 22 genotypes. A significant variation among genotypes was observed for the characteristics fruit length and mass. Regarding firmness of fruits with peel, 12 genotypes showed higher firmness than the Tainung Nº 1 and Sunrise Solo cultivars. Correlation analysis showed that fruits with greater length, diameter, and internal cavity diameter tend to have greater weight and pulp thickness, whereas fruits with higher soluble solids tend to have higher soluble solids/titratable acidity ratio, vitamin C, and total carotenoids. The L72 inbred line of the Solo group and the H36.45 hybrid of the Formosa group present fruit with physical and physicochemical characteristics similar or superior to those of the Sunrise Solo and Tainung Nº 1 commercial cultivars, respectively, and, therefore, are promising to the market.